Fiqh Muamalah Analysis of the Fundraising Zakah through Conventional Bank Accounts - Imam Kamaluddin; Vina Fithriana Wibisono; Andini Rachmawati; May Shinta Retnowati; Fawwaz Raihan (Jurnal Hukum Islam, 2023)
Collecting zakah funds through conventional banks is vulnerable to elements of usury. Whereas, Islamic legal norms have strictly regulated that all assets must be protected from the element of usury, including Zakah funds. This research analyzes the collection of zakah funds by zakah fund collection institutions which is carried out by giving muzaki (zakah givers) the option to transfer zakah funds using conventional bank accounts. This paper discusses two schemes,i.e: first, the mechanism for collecting zakah funds through conventional bank accounts; second, analyzing the collection of zakah funds from the perspective of Muamalah Fiqh, namely using the Tabarru agreement. The research method uses empirical juridical with a qualitative approach.  The results show,  the mechanism for collecting zakah funds through conventional bank accounts is that muzakki are given the option to transfer zakah funds to a conventional bank account or sharia bank,  which is owned by the institution collecting zakah funds; then the institution collecting zakah funds separates the bank interest from conventional banks for the public needs, such as building roads, public toilets, bridges, etc; and finally distributing it to Mustahiq. According to Fiqh Muamalah, the factors that cause a transaction to be haram are haram because of its substance, haram in addition to its substance and the cancellation of the contract. Meanwhile, the permissibility of a haram transaction must be channelled for social benefit, because this action is better than entrusting non-halal funds to a Sharia Bank.